Predictors of Postoperative Nausea and Vomiting After Endoscopic Skull Base Surgery. (25th October 2021) - Birkenbeuel, Jack L.; Warner, Danielle C.; Abiri, Arash; Brown, Nolan J.; Nguyen, Emily S.; Lee, Ariel; Goshtasbi, Khodayar; Boladian, Lana A.; Hsu, Zachary; Bitner, Benjamin F.; Golshani, Kiarash; Chen, Jefferson W.; et al.
Abstract : Objectives/Hypothesis: The objective of this study is to evaluate the impact of patient and surgical factors, including approach and reconstruction type, on postoperative nausea and vomiting episodes following endoscopic skull base surgery. Study Design: Retrospective review. Methods: We performed a retrospective chart review from July 2018 to August 2020 of 99 consecutive patients undergoing endoscopic skull base surgery at a tertiary academic skull base surgery program. All patients were treated with a standardized postoperative protocol consisting of scheduled ondansetron, along with promethazine and scopolamine for breakthrough nausea and vomiting episodes. Cumulative nausea and vomiting episodes throughout hospital stay were recorded for each patient. Results: Of the 99 patients identified, the mean number of nausea and vomiting episodes per patient were 0.4 ± 1.2 and 0.3 ± 0.7, respectively. Female sex ( β = .65, P = .034) and extended surgical approach ( β = .90, P = .027) were associated with increased risk for postoperative nausea. Furthermore, female sex ( β = .44, P = .018), cavernous sinus dissection ( β = .52, P = .002), and extended approach ( β = .79, P = .025) significantly increased odds of postoperative vomiting episodes. There was no association between total operative time or total postoperative opioid dose and nausea and vomiting episodes (all P s > .05). Neither increased nausea nor vomiting episodes significantly increased odds of prolonged hospitalization ( P = .105 and .164, respectively). Conclusion: This report highlights novel risk factors for patients undergoing endoscopic skull base surgery. Upfront standing antiemetic therapy may be considered when treating patients with independent predictors of postoperative nausea and vomiting, including female sex, cavernous sinus dissection, and extended surgical approach. Level of Evidence: 4 Laryngoscope, 132:761–768, 2022